Updates in the Management of Chronic Pancreatitis: Navigating Through Recent Advances - Vanek, Petr; Freeman, Martin L (Gastroenterology clinics of North America, 2025)
This article provides an up-to-date review of the management of chronic pancreatitis, highlighting advancements in medical therapy, nutritional support, endoscopic and surgical approaches, and emerging treatments. Nutritional management accentuates addressing malabsorption and nutrient deficiencies. Advances in endoscopy and parenchyma-sparing surgical techniques have opened new avenues for improved patient outcomes, with total pancreatectomy and islet autotransplantation offering the only definitive solution for selected patients. Additionally, emerging therapies, including anti-inflammatory and immune-modulating agents, show promise for future treatment options. Emphasizing a multidisciplinary approach, this review aims to equip health care professionals with a comprehensive overview of current management strategies and future directions.
Keywords: transplantace Langerhansových ostrůvků; Pancreatitis, Chronic; chronická pankreatitida; Islets of Langerhans Transplantation; nutriční podpora; lidé; pankreatektomie; Humans; Pancreatectomy; Nutritional Support